Lenalidomide-Associated Immune Thrombocytopenia: A Case Report and Review of the Literature - Forehand III, William (Case Rep Hematol, 2020)
Lenalidomide is indicated in the front-line management of multiple myeloma. More recently, it has been introduced for use in treating other hematologic malignancies. Although the drug is known to cause myelosuppression, there have been rare reports of lenalidomide-associated immune thrombocytopenia (ITP). Here, we review the literature on lenalidomide-associated ITP and report upon a 59-year-old man who was administered lenalidomide due to concern of progressive multiple myeloma more than a year following his having undergone an autologous hematopoietic stem cell transplant. His platelet count precipitously declined and lead to his hospitalization. Despite our withholding of the drug, he did not respond to platelet transfusions or administration of corticosteroids. He was successfully managed with intermittent immune globulin for several months before definitive treatment with splenectomy, which resulted in the complete resolution of his thrombocytopenia. A literature search identified a total of six additional cases of lenalidomide-associated ITP. Similarly, many of the reported cases were associated with persistent thrombocytopenia after discontinuation of the drug. Furthermore, these patients were generally managed successfully with standard ITP therapies, such as corticosteroids or intravenous immune globulin.